Hadron-Nucleus interactions in the nucleon resonance region - Geßler, Stefanie; Justus Liebig University Giessen (My University, 2017)
Experiments with high-energy hadron beams have found renewed attention. In the near future nuclear studies with hadron beams are planned at least at two facilities, namely J-PARC in Japan and GSI/FAIR. The aim of this work is an exploratory investigation of interactions of mesons and baryons with nuclei at energies of interest for future research with antiprotons at FAIR.The theoretical discussion is started with an introductory presentation of the optical model and Eikonal theory as appropriate tools for the description of scattering processes at high energies. In antiproton interactions with nucleons and nuclei, annihilation processes into pions are playing the major role for the reaction dynamics. Therefore, we consider first the interactions of pions with nuclei by deriving an extended selfenergy scheme for a large range of incident pion energies. In order to have a uniform description over a broad energy interval, the existing approaches had to be reconsidered and in essential parts reformulated and extended. A central result is the treatment of pion-nucleus self-energies from high lying N* resonances. Only by including those channels in a proper manner into the extended pion optical potential, pion-nucleus scattering could be described over the required large energy range. At low energies the well known Kisslinger potential is recapped.Next, the same type of reaction theory is used to analyze antiproton-nucleon and nucleus scattering from low to highly relativistic energies. The reaction dynamics of antiproton interactions with nuclear targets is discussed. We start with a new approach to antiproton-nucleon scattering. A free-space antiproton-nucleon T-matrix is derived, covering an energy range as wide as from 100 MeV up to 15 GeV. Eikonal theory is used to describe the antiproton scattering amplitudes in momentum and in coordinate space. We consider, in particular, interactions with nuclei at energies around and well above 1 GeV. The antiproton-nucleus self-energies are obtained microscopically in a folding model using the previously derived T-matrix interactions and nuclear ground state densities form HFB calculations. For a quantitative description, an extended eikonal reaction theory is used.Finally, an outlook is given to applications of the results as ISI and FSI in pion production in antiproton annihilation on nuclei. Two reaction scenarios are identified and studied in exploratory calculations.

Experimente mit hochenergetischen Hadronenstrahlen sind erneut von großem Interesse. In naher Zukunft sind mindestens zwei neue Experimente mit hochenergetischen Hadronenstrahlen geplant: J-PARC in Japan und FAIR in der GSI an Darmstadt. Ziel dieser Arbeit ist es die Wechselwirkung von Mesonen und Baryonen mit Atomkernen exemplarisch zu untersuchen in Energiebereichen, die relevant für zukünftige Forschung mit Antiprotonen an der FAIR Beschleunigeranlage sind.Die Arbeit beginnt mit einer einführenden Diskussion der zugrundeliegenden Theorien, wie die des optisches Potentials und der Eikonaltheorie, als passende Werkzeuge zur Behandlung von hochenergetischen Streuproblemen. Hauptteil der zugrundeliegenden Reaktionsdynamik von Antiprotonen Wechselwirkungen mit Nukleonen und Atomkernen sind Annihilationsprozesse, die in der Erzeugung von Pionen resultieren. Aus diesem Grund betrachten wir zunächst die Wechselwirkung von Pionen mit Kernen und erweitern die zugrundeliegenden Selbstenergien zur Beschreibung eines großen Spektrums von eingehenden Pionenenergien. Um eine einheitliche Beschreibung über große Energiebreiche zu erhalten, wurden bereits existierende Ansätze zusammenfassend betrachtet und schließlich essentielle Teile neu formuliert und erweitert. Ein zentrales Ergebnis ist die Behandlung der höheren Resonanzen in Pion-Kern Selbstenergien. Nur durch Einbinden dieser Resonanzen in ein erweitertes optisches Potential konnte die Streuung von Pionen mit Kernen korrekt über weite Energiebereiche beschrieben werden. Für niedrige Energien wird das bekannte Kisslinger-Potential vorgestellt.Als nächstes wurde innerhalb derselben Reaktionstheorie Antiproton-Nukleon und Antiproton-Kern Streuung von niedrigen bis zu relativistischen Energien analysiert. Ein neuer Ansatz zur Beschreibung von Antiproton-Nukleon-Streuung wird präsentiert. Die Antiproton-Kern T-Matrix wird mit einem Ansatz gerechnet, der eine Beschreibung von einem Energiebereich von wenigen MeV bis zu 15 GeV ermöglicht. Die Eikonaltheorie wird dazu genutzt, die Streuamplitude sowohl im Orts- als auch im Impulsraum zu berechnen. Die Antiproton-Kern Selbstenergien werden durch Faltung der Grundzustandskerndichte, Ergebnis von HFB Berechnungen, und der zuvor erwähnten T-Matrix berechnet. Im Ausblick werden schließlich die Anwendungen dieser Rechnungen als Input für Eingans- und Ausgangskanalwechselwirkungen komplexer Reaktionen diskutiert: der Pionproduktion bei Antiproton-Annihilation im Kern. Zwei Reaktionsszenarien werden vorgestellt und exemplarische Berechnungen präsentiert.
Hadronen-Kern-Wechselwirkungen in der Resonanz-Region des Nukleons
Keywords: Hadronen; Kern; Wechselwirkung; Resonanz; hadrons; nucleus; interactions; resonance; ddc:530